Literature Review: The Potential Activity of Secondary Metabolite Compounds in The Rutaceae Family Plants Against Streptococcus Mutans - Elvariani, Ni Wayan Dessy Risma; Frethernety, Agnes; Furtuna, Dewi Klarita (Fakultas Kedokteran Universitas Palangka Raya, 2025)
Dental caries is caused by Streptococcus mutans, with resistance to fluoride becoming a significant challenge, thus requiring new antibacterial alternatives. The purpose of this literature review is to examine the potential of metabolite compounds from the Rutaceae plant family against S. mutans through a systematic review. The method used includes a literature review from databases such as Google Scholar, PubMed, and Research Gate (2014–2024) following the PRISMA protocol. The analysis covers plants from the Rutaceae family, bacterial inhibition zone tests, and secondary metabolite content. A total of 15 journals (6 national, 9 international) demonstrated that the Rutaceae family plants possess strong antibacterial activity. Active compounds such as flavonoids, alkaloids, tannins, saponins, and terpenoids were found in the bark, leaves, and fruits of the plants. Extracts from the bark of Citrus aurantifolia showed the largest inhibition zone against S. mutans (28.7 mm). Flavonoids and tannins played a significant role in antibacterial activity. The conclusion derived is that the Rutaceae family has great potential as a natural antibacterial agent for the prevention of dental caries. These findings provide a foundation for developing safe and effective oral care products based on natural ingredients. Further research, particularly in the formulation of safe and effective natural-based oral care products